Pengaruh Kualitas Produk dan Pelayanan Terhadap Keputusan Pembelian - Khayru Aqillah; Ririn Virnanda; Dian Purnama Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
D’Celup Chicken Crispy is a well-known fried chicken culinary brand in Indonesia, recognized for its crispy fried chicken and diverse sauce options that attract consumers. In this context, the company must be able to observe consumer behavior that influences purchasing decisions as part of its marketing efforts. Therefore, this study aims to examine the influence of product quality and service quality on purchasing decisions, with active customers of D’Celup Chicken Crispy Medan as the research object. The research was conducted at six branch locations of D’Celup Chicken Crispy in Medan City, from May 28, 2025, to June 8, 2025. This study employed a quantitative descriptive research method. Sampling was carried out using purposive sampling to target respondents who met the criteria, drawn from a population of 58 using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression. The analytical tool used was IBM SPSS Statistics 26. The findings reveal that both product quality and service quality have a positive and significant effect on purchasing decisions simultaneously. Furthermore, it is also proven that product quality has a positive and significant effect on purchasing decisions, as does service quality.